OPTIMIZATION OF DATA TRANSFER IN THE INTERNET OF THINGS ENVIRONMENT - Rastislav PETIJA (Technical University of Kosice, 2021)
This article deals with the implementation and experimental verification of the suitability of the TinyIPFIX protocol for data transmission in the Internet of Things environment. The work was devoted to the creation of three main components, namely TinyIPFIX exporter, collector, and mediator. The implementation of these tools made it possible to extend the possibility of monitoring a common network with an IoT environment. The experiments confirmed the success of the implementation of the protocol based on standards and pointed out the suitability of the implementation of the TinyIPFIX protocol mainly due to its optimized processes, which save up to 72% of bandwidth consumption compared to the IPFIX protocol when transmitting one data unit. Thanks to the modular approach during implementation, it is possible to deploy the protocol in the environment regardless of the transport technology. The created solution can therefore also be used in UAV sensor networks.